2005
DOI: 10.1007/s00268-005-7531-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Long‐term Graft Survival after Kidney Transplantation: Multicenter Study in Japan

Abstract: A multicenter retrospective study was conducted in 936 living donor kidney transplant recipients treated with cyclosporine (CsA) or tacrolimus (FK) from April 1982. The influences of acute rejection, hyperlipidemia, and hypertension were estimated by Kaplan-Meier's analysis and Wilcoxon's analysis. Of 916 recipients, 532 (58.1%) had acute rejections. The 5- and 10-year graft survival rates in the recipients with acute rejection were 75.2% and 55.2%, respectively. The corresponding rates of the recipients witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
1
12
0
6
Order By: Relevance
“…The consequences of hypertension are serious and include poorer renal function (39) and diminished patient/graft survival (40,41). For example, a retrospective analysis of kidney transplant patients found that each 10 mm Hg increase in posttransplant systolic blood pressure was associated with a 10% to 20% increased risk for graft failure and death (12).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of hypertension are serious and include poorer renal function (39) and diminished patient/graft survival (40,41). For example, a retrospective analysis of kidney transplant patients found that each 10 mm Hg increase in posttransplant systolic blood pressure was associated with a 10% to 20% increased risk for graft failure and death (12).…”
Section: Discussionmentioning
confidence: 99%
“…36 Entretanto, a magnitude do aumento nas concentrações médias de colesterol e triglicérides foi pequena, apesar de maior entre os pacientes recebendo CSA, com tendência à redução após o primeiro ano do transplante. 7,16 Finalmente, apesar da possibilidade de interferência do SRL sobre o metabolismo de carboidratos, a concentração média de glicose ficou dentro dos limites de normalidade, não se observando diferença entre os pacientes que receberam CSA ou TAC.…”
Section: Discussionunclassified
“…The benefit of maintenance steroids did not seem to be as pronounced when the 1st AR episode was moderate/severe or had a humoral component-but even in these groups there seemed to be some advantage to maintenance steroids. This potential for increased risk of a 2nd AR episode in those recipients that remained steroid free is of obvious concern because of the negative impact of multiple rejection episodes on longterm graft survival (15)(16)(17). Also of concern is the fact that 5 of the 81 recipients that remained steroid free eventually went on to graft loss because of a repeat AR episode.…”
Section: Discussionmentioning
confidence: 99%